THE CRITICAL THEORY OF HISTORY: RETHINKING THE PHILOSOPHY OF HISTORY IN THE LIGHT OF KOSELLECK'S WORK. Issue 2 (May 2016) - BOUTON, CHRISTOPHE
ABSTRACT: There are many ways to consider the philosophy of history. In this article, I claim that one of the most viable approaches to the philosophy of history today is that of critical theory of history, inspired by Reinhart Koselleck. Critical theory of history is based on what I call known history, history as it has been established and expounded by historians. What it contributes—its added value, so to speak—is a reflection on the categories employed to think about historical experience at its different levels, not only as a narrative but also as a series of events: their origins, contexts, terminology, functions (theoretical or practical), and, finally, eventual relevance.